Analysis of the Multiplier Effect of Geopolitical Conflict on the Indonesian Economy and its Mitigation Strategy - Makruf, Anang Nur; Riani, Lilia Pasca (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The main objective of this study is to deeply analyze the multiplier effect of geopolitical conflicts on Indonesia's economic balance. This research specifically focuses on critical sectors such as international trade, finance, and real industry. Design/Methode/Approach : This research uses a literature review method with a descriptive qualitative approach. Literature review was chosen because this research aims to analyze the impact of geopolitical conflicts on Indonesia's economic balance through the study of various scientific sources, secondary data, and economic reports. The descriptive qualitative approach is used to understand and explain the relationship patterns between geopolitical conflicts and national economic Research Finding : This study shows that global geopolitical conflicts have a significant impact on the Indonesian economy. Preliminary findings show that there are serious disruptions to global supply chains, which then trigger an increase in domestic inflation. In addition, the geopolitical conflict also contributed to the weakening of the rupiah exchange rate. Overall, these impacts collectively negatively affect people's purchasing power and hamper the pace of national economic growth. Theoretical contribution/Originality : This study analyzes the multiplier effects of geopolitical conflict in the specific context of Indonesia, which may contribute to further understanding of how global instability affects emerging economies. Its originality lies in analyzing the impact in the specific context of Indonesia and possibly in integrating various interrelated economic impacts. Practitionel/Policy implication : This research clearly underscores the importance of developing and implementing effective mitigation strategies to maintain Indonesia's economic stability. The research results are expected to provide valuable insights for policymakers and economic actors in formulating adaptive, resilient and sustainable policies in the face of global geopolitical challenges. It shows significant practical implications for economic policy-making in Indonesia. Research limitation : The limitations of this study include the complexity and variability of geopolitical conflicts that make it difficult to accurately measure the impact, challenges in the availability of specific data for multiplier effects, potential dependence on economic model assumptions, possible scope limitations on specific sectors or timeframes, as well as limitations in Indonesia's economic policy mitigation strategies.